ś.p. ks. dr Kazimierz Obrycki (1941-2019) - Kalinkowski, Stanisław (Vox Patrum, 2019)
Posthumous memory of Rt. Rev. Dr. Kazimierz Obrycki, a classical philologist, translator of the works of the Church Fathers and a patrologist.